Sexist Humour and the Acceptance of Sexual-Aggression Myths: The Moderating Roles of Gender and Humour Beliefs - Akbar, Husna; Elahi, Kinza Naseem; Kaiser, Maliha; Arshad, Umama; Mehmood, Khudeja (Journal of Gender Related Studies, 2025)
Purpose: The present research aimed to explore the impact of sexist humour on the acceptance of sexual aggression myths, with a specific focus on the moderating roles of the joke teller’s gender and cavalier humour beliefs (CHB). Methodology: A quantitative experimental design was used with a 2 (joke type: sexist, neutral) × 2 (joke teller’s gender: male, female) fully between subjects structure. A total of 308 Pakistani university students aged 18 to 29 were recruited through convenience and voluntary response sampling. Participants were presented with joke stimuli via an online Qualtrics survey and completed standardized measures assessing their humour beliefs and acceptance of sexual aggression myths. Findings: Contrary to the original hypothesis, exposure to sexist jokes compared to neutral jokes resulted in lower acceptance of sexual aggression myths. Additionally, participants with medium to high CHB found sexist jokes significantly more amusing when told by a female joke teller. These findings diverge from Western literature that typically reports reinforcing effects of sexist humour, and instead suggest a more complex relationship between humour, identity, and cultural context. In collectivist societies, such humour may activate moral reflection or critique rather than reinforcement of harmful beliefs. Unique Contribution to Theory, Policy and Practice: This research contributes new insights into how humour operates within a South Asian cultural framework. By demonstrating that sexist humour may, under certain conditions, reduce the acceptance of harmful myths, it challenges dominant theories developed in Western contexts. These findings offer practical implications for awareness campaigns and educational efforts in societies where humour is socially embedded. They also inform policy by emphasizing the importance of culturally grounded approaches to combating gender based prejudice.